1973
DOI: 10.1007/bf02502921
|View full text |Cite
|
Sign up to set email alerts
|

Complexing capacity of the nutrient medium and its relation to inhibition of algal photosynthesis by copper

Abstract: The toxic effect of copper on phytoplankton production is investigated in waters having different complexing capacities. It is demonstrated that a water's complexing capacity does not guarantee that an equivalent amount of copper could be tolerated without adversely affecting algal production. Possible explanations for these findings axe offered and discussed.It is deduced that ionic copper probably is already toxic to planktonic algae at concentrations of about 10 -t~ mole/1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
11
0
2

Year Published

1977
1977
2004
2004

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 19 publications
3
11
0
2
Order By: Relevance
“…Shuman and Michael (13) suggested that electrode processes at the mercury droplet may obscure the true nature of interactions of cupric ion with natural organic ligands. In addition, Gachter et al (14) suggested that a chemical measurement of natural complexation capacity of a water sample does not by itself guarantee that an equivalent amount of copper can be tolerated without an adverse effect on phytoplankton production.…”
Section: Introductionmentioning
confidence: 99%
“…Shuman and Michael (13) suggested that electrode processes at the mercury droplet may obscure the true nature of interactions of cupric ion with natural organic ligands. In addition, Gachter et al (14) suggested that a chemical measurement of natural complexation capacity of a water sample does not by itself guarantee that an equivalent amount of copper can be tolerated without an adverse effect on phytoplankton production.…”
Section: Introductionmentioning
confidence: 99%
“…Most work has involved laboratory experiments rather than field studies, and comparatively little is known about the complexation capacities and metal-binding specificities of natural ligands in freshwater ecosystems generally or the North American Great Lakes in particular. Pioneering work in this respect was conducted originally by Chau et al (1970) and Gächter et al (1973). The latter authors demonstrated that despite apparent excess complexing capacity for Cu of several hundred nanomoles per litre in waters from Lake Ontario, the Niagara River, and Hamilton Harbor, additions of as little as 100 nmol·L -1 Cu reduced carbon fixation substantially.…”
Section: Introductionmentioning
confidence: 98%
“…Phytoplankton growth experiments by Barber (3) demonstrated significant response to small additions of both metals and chelators. These and stmilar observations led G~chter, Lum-Shue-Chan and Chau (4) to conclude that the free copper ion and its inorganic complexes are more toxic than are its organic ccmplexes.…”
mentioning
confidence: 99%